Adoption of striga (striga hermonthica) Management Technologies in Northern Nigeria. Issue 1 (2nd April 2016) - Hassan, M.B.; Baiyegunhi, L.J.S.; Ortmann, G. F.; Abdoulaye, T.
ABSTRACT: This study examined the adoption of Integrated Striga Management (ISMA) technologies among maize farmers in Bauchi and Kano states of northern Nigeria. It employs a double-hurdle approach to analyse the factors influencing adoption and intensity of ISMA technologies among households, using cross-sectional data of 643 farmers from the two states. The results show that the estimated coefficients of exogenous income and proximity to extension office are negatively significant ( P < 0.05), while higher total farm income, polygamous households, past participation in on-farm trials, awareness of the technology, contact with extension agents and access to cash remittances are positive and significant ( P < 0.01), and are the most significant factors likely to influence ISMA technologies adoption. Marital status, household size, farm size and access to cash remittances are most significant factors influencing adoption intensity. Maize farmers in the study area who adopted ISMA technologies obtained higher output than the non-adopters, which resulted in a positive and significant effect on their total farm income. Hence, policies targeted at increasing maize productivity through Striga management need to include ISMA technologies as a potentially feasible option. The study recommends actions to improve farmers' access to financial services to increase their liquidity. Nevertheless, the most immediate action will be improvement in farmers' access to extension services as they have proved to be a reliable source of information in the rural areas.